'n Semiotiek van asiel/sitbetoging: - N.J.C. van den Berg (Communicare)
This research has as its theme the sit-in by three persons staged in the USA consulate in Johannesburg in 1988. The event is studied from a semiotic perspective. The semiotic 'model' followed is eclectic as it is constituted by views drawn from inter alia Heidegger, Gadamer, Ricoeur, Benson, and particularly Eco. Two main readers were involved in the event, i.e. the governments of South Africa and the United States of America. The interpretation of the event by both governments cre ated a specific 'perception'/meaning in the minds of South Africa's (and the world's) population. This re search strives to establish which country's interpretation was ac cepted by the population in South Africa.